Distribution and morphology of polygons, South Polar Region, Mars - van Gasselt, S.; Reiss, D.; Jaumann, R. (Lunar and Planetary Institute, 2003)
In this work we present a mapping of polygonal patterns at the south pole of Mars between 80°-90° S on the basis of all MOC narrow angle images (up to the current release of E18). We found 750 (out of 6000) MOC narrow angle images showing a variety of polygonal patterns resembling terrestrial ice wedge polygons. They occur predominately inside circular depressions of the polar layered deposits, circum polar troughs and re–entrants or below slopes.